Liming effect on the response and nitrogen symbiotic fixation of common bean (Phaseolus vulgaris L.). - García, Aurelio; Dueñas, Graciela; Hernández, Germán; Herrero, Grisel; Nuviola-Montoya, Antonio; Méndez, Nancy; Zapata, Felipe (Agronomía Mesoamericana, 2003)
A glasshouse experiment was conducted in order to evaluate, using the A value method, the liming effect on the efficiency of nitrogen symbiotic fixation (NSF) of the common bean genotypes BAT 58, BAT 477, DOR 364 and CC 25-9 (N) in a Rhodic Ferralsol soil. NN 125, a non nodulant common bean, was used as the control crop. All common bean genotypes increased the fraction of N in plant derived from soil due to liming, mainly CC 25-9(N), that show a very low capacity to fix N from air if the soil is not amended with lime. Moreover, a beneficial effect of liming on the soil N pool was found, because the increasing total N uptake by plants was due to the N coming from the air, and the quantity of N in plant coming from the soil diminished, mainly for DOR 364 and CC 25-9(N). In addition, the ratio %Ndff/%Ndfs, the N percentage in plant derived from the fertilizer and derived from the soil, respectively, vary due to the N percentage liming. Therefore, it is necessary to use two treatments for the control in order to evaluate accurately the NSF: with and without the lime application. The Nitrogen Use Efficiency parameter is disscused.